Limits of Number of Motes at Smart City Scenarios for LoRaWAN - Catak, M.; Celikkaya, B. (Engineering, Technology & Applied Science Research, 2019)
LoRaWAN is an emerging technology as a solution to IoT sensor networks. Since it is still in the evolvement stage, academic and industrial researches and applications have to be conducted in order to analyze its limitations and possible improvements. In this paper, the number of motes that could transmit data to a gateway within a 95% confidence interval has been studied under a number of scenarios. According to the results, the most significant parameter regarding the number of motes is the period of the downlink signal.